(untitled) (Latakia University Journal -Medical Sciences Series, 2016)
The objective of this study was to study and to analyze caffeine release from gel and emulgel prepared from carbopol. The properties of the preparations were determined (e.g. visual inspection, pH test, spreadability and in vitro release). The mechanisms of caffeine release were analyzed according to zero and first orders, and to Higuchi and Korsmeyer-Peppas models. Results were analyzed statistically using student t-test. The gels were transparent while emulgels were creamy, white and smooth. pH values were suitable for dermal application and spreadability was not changed in both cases. On the other hand, accumulated released amount of caffeine was decreased from emulgel in comparison with the gel. The release pattern was in accordance with Higuchi equation and n value referred that the diffusion was the main mechanism of release from the gel while the relaxation and the erosion contributed importantly in the release of suspended caffeine from emulgel. تهدف هذه الدراسة إلى دراسة سلوك تحرر الكافئين من هلاميات وهلاميات استحلابية (emulgels) محضرة بواسطة الكاربوبول. حددت خواص المستحضرات الناتجة من حيث الفحص العياني, فحص الـ pH, فحص القدرة على المد وفحص التحرر. درست حركية تحرر الكافئين من هذه الهلاميات وفق الرتبة صفر والأولى ووفق نموذج Higuchi ونموذج Korsmeyer- Peppas. استخدم اختبار ستيودنتt-test لتحليل النتائج إحصائياً عند مستوى دلالة 0.05. كانت الهلاميات شفافة بينما كانت الـ emulgels بيضاء وناعمة ولماعة. كانت قيم الـ pH مناسبة ولم تتأثر قابلية الهلامة للمد عند تحويلها إلى emulgel بإضافة زيت البارافين. من جهة أخرى, نقصت كمية الكافئين المتحررة الكلية بدءاً من الـ emulgel بالمقارنة مع الهلامة العادية وكان التحرر في كلتا الحالتين وفق نموذج Higuchi وأشارت قيمة n إلى أن التحرر كان بشكل أساسي بواسطة الانتشار في حالة الهلامة الحاوية على كافئين منحل بينما ساهم الاسترخاء بشكل هام في تحرر الكافئين المعلق في الـ emulgel.